Analysis of the Effect of Tax Rates and Understanding of Taxation on MSME Taxpayer Compliance in Lamongan Regency - Saputri, Rizka Dibi Arryanti; Nugraha, Farhani Kautsar (Review: Journal of Multidisciplinary in Social Sciences, 2024)
MSMEs are one sector that has the potential to contribute to state tax revenues. This research aimed to examine the influence of tax rates and tax understanding on the level of taxpayer compliance in Micro, Small and Medium Enterprises (MSMEs) in the Lamongan Regency. Through a survey approach using a questionnaire, primary data was got from MSME owners as a research sample of 94 respondents. The results could provide a deeper understanding of the factors that influence tax compliance among MSMEs, especially in the Lamongan Regency. Regression analysis was used to test the relationship between tax rate variables, tax understanding, and the level of tax compliance. The results could provide a deeper understanding of the factors that influence tax compliance among MSMEs simultaneously or partially, especially in the Lamongan Regency. The implication of these findings was the importance of managing proportional tax rates and effective tax counseling to encourage MSME taxpayer compliance in the Lamongan Regency. This research contributed to further understanding of tax factors that could form a better tax environment for MSME growth and Regional Tax revenues.